(untitled) (Communications in Computational Physics, 2020)
Water management in gas diffusion layer (GDL) and micro porous layer (MPL) poses a great impact on performance of proton exchange membrane fuel cells (PEMFCs). And enhancement of the performance of fuel cells requires an appropriate water balance between the conservation of membrane humidity and the discharge of excess water produced in the cell. The Lattice Boltzmann method (LBM) can enable more straight simulation of fluid flow with complex solid structures, compared with conventional computational fluid dynamics (CFD) method based on Navier-Stokes equations. In this study, the orthorhombic pseudo-potential multiphase lattice Boltzmann method (LBM) is used to investigate liquid water transport in the MPL and GDL of polymer electrolyte membrane fuel cells (PEMFC). And the GDL and MPL structure images are all acquired by the stochastic generation method. We compared the GDL coated by the MPL with different thickness and different porosity. Numerical results confirm that influence of porosity is much greater than the thickness, which can help to improve the GDL and MPL design.